Glutamate receptor 4 as a fluid biomarker for the diagnosis of psychiatric disorders. (December 2022) - Gómez de San José, Nerea; Goossens, Julie; Al Shweiki, Mhd Rami; Halbgebauer, Steffen; Oeckl, Patrick; Steinacker, Petra; Danzer, Karin M.; Graf, Heiko; Schönfeldt-Lecuona, Carlos; Belbin, Olivia; Lleó, Alberto; Vanmechelen, Eugeen; et al.
Abstract: Psychiatric disorders are widely underreported diseases, especially in their early stages. So far, there is no fluid biomarker to confirm the diagnosis of these disorders. Proteomics data suggest the synaptic protein glutamate receptor 4 (GluR4), part of the AMPA receptor, as a potential diagnostic biomarker of major depressive disorder (MDD). A novel sandwich ELISA was established and analytically validated to detect GluR4 in cerebrospinal fluid (CSF) samples. A total of 85 subjects diagnosed with MDD (n = 36), bipolar disorder (BD, n = 12), schizophrenia (SCZ, n = 12) and neurological controls (CON, n = 25) were analysed. The data exhibited a significant correlation (r = 0.74; CI:0.62 to 0.82; p < 0.0001) with the antibody-free multiple reaction monitoring (MRM) mass spectrometry (MS) data. CSF GluR4 levels were lower in MDD (p < 0.002) and BD (p = 0.012) than in CON. Moreover, subjects with SCZ described a trend towards lower levels than CON (p = 0.13). The novel GluR4 ELISA may favour the clinical application of this protein as a potential diagnostic biomarker of psychiatric disorders and may facilitate the understanding of the pathophysiological mechanisms behind these disorders. Highlights: Glutamate receptor 4 as a novel CSF biomarker in the diagnosis of psychiatric disorders. The sample comprised major depressive disorder, bipolar disorder and schizophrenia. A novel sandwich ELISA to detect GluR4 in CSF samples was developed and validated. Patients with MDD and BD presented lower GluR4 levels in CSF than controls. The data correlated with the published targeted mass spectrometry findings.